Epidemiology, Pathophysiology and Symptomatic Treatment of Sciatica: A Review - Kumar, Manish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT: Sciatica refers to pain, weakness, numbness or tingling in the leg. Sciatica is a relatively common condition with a lifetime incidence varying from 13% to 40%. The common corresponding annual incidence of an episode of sciatica ranges from 1% to 6 %. This review assesses current knowledge of the epidemiology, pathogenesis and treatment of sciatica.